A Catalyst‐Based Self‐Sufficient System with Durable Self‐Healing Functionality1 . Issue 6 (16th December 2015) - Sun, Wen; Wang, Lida; Wu, Tingting; Zhu, Tianzhen; Xie, Hongbin; Pan, Yanqiu; Liu, Guichang
Abstract : A novel self‐sufficient self‐healing system for metal protection is demonstrated in this work. The system is sustainable and can provide effective and durative protection for metal through autonomously healing the protective layer on metal surface while without adding any additional consumable reagents or external powers. As the system is fabricated on the basis of stable oxygen reduction reaction catalyst, the self‐healing process can be repeated many times. Furthermore, the combination of catalyst‐induced repeatable self‐healing of metal passivation and serviceability of polymers makes this system ideal for intelligent metal protection. Abstract : A novel self‐healing system which is capable of repeatedly restoring the protection barrier for metals is demonstrated. The system is sustainable, self‐sufficient, and can autonomously provide effective and durative protection for metals through utilizing available conditions in the environment surrounding coating defects, while without adding any additional consumable reagents or external powers.